INDUSTRY 4.0 IN WELDING PROCESSES IN THE AUTOMOTIVE INDUSTRY - Mihăiță-Nicolae COMAN; Corneliu RONTESCU; Ana-Maria BOGATU; Dumitru-Titi CICIC; Adrian FLOREA (Fiabilitate şi Durabilitate, 2023)
In the current context of industry development through the implementation of the concepts of Internet of Things (IoT), Big Data, Artificial Intelligence technology, welded structures manufacturing processes must adapt to the new trends. The main advantages of implementing these concepts in the industry consist of increasing process efficiency, increasing productivity and achieving better management through product customization, intelligent monitoring applications for production and machine health, and predictive and preventive maintenance of industrial equipment. Thus, intelligent welding manufacturing and systems (IWMS) should be the norm for manufacturing systems. The paper presents the implementation of four new robotic cells, with the possibility of online monitoring and control of all their equipment. Moreover, all the information necessary for the manufacturing process as well as all the documents elaborated are available in Cloud and can be permanently accessed by authorized persons. Starting with the process of design, elaboration of technical documentation, welding, control up to packaging and delivery to the beneficiary, all the activities are standardized and the status of the manufacturing process can be supervised.